Compulsory Incentivized Organ Donation: A Case for a Fairer Organ Donor Policy in Ontario - Gite, Jasmine; Sukumar, Niron (The Meducator, 2014)
Ontario, like many other countries around the world, follows a voluntary organ donor system. Citizens are given the option of becoming donors at the age of 16 and are scarcely reminded of the option ever after. As such, less than a quarter of Ontarians are registered organ donors. Not only is this an unnecessary waste of precious organs, it is also an extremely unfair system, as both donors and non-donors are considered of equal priority to receive organ transplants. We thus call for a compulsory incentivized organ donationsystem in Ontario, as a fairer and more efficient organ donor policy. This policy automatically considers all citizens as organ donors after a certain age, where unwilling citizens can opt out if they wish to do so. However, individuals that choose to opt out are given less priority for organ transplants as compared to those who remain as organ donors. By automating organ donor registration and providing disincentive to opt out of organ donation, such a policy ensures a greater availability of organs for all Ontarians.